The needs of aircraft avionics’ radio line replaceable unit repair center at UniKL MIAT - Wasi Zainal Ariffin, Muzzaffar; Khudri Johari, Muhd; Ibrahim, Hashim (International Journal of Engineering and Technology, 2018)
For the local aircraft maintenance industry, radio line replaceable unit (LRU) has been essential in aircraft’s airworthiness but at the same time, costly for many Malaysian aviation companies. This study analyzes the survey conducted with 66 aviation industry personnel from 11 local aviation companies, which have had to spend a considerable amount of financial budget on their LRU maintenance every year. The conclusion from the survey data shows that most of them agreed on the need to establish an LRU Center in a local approved training organization such as Universiti Kuala Lumpur – Malaysian Institute of Aviation Technology (UniKL MIAT) because of several justifiable reasons such as significantly cheaper costs, more hands-on training and job opportunities, shorter delivery time, and possible research and development benefits.